PERSEPSI MASYARAKAT TERHADAP KUALITAS LAYANAN PUBLIK YANG DIBERIKAN OLEH INSTANSI PEMERINTAH DI KABUPATEN SLEMAN DAN KABUPATEN BANTUL - Murtin, Alex (Journal of Accounting and Investment, 2008)
The study is focused on the difference of perception between the society government officials on service quality in Bantul and Sleman regency DIY. The sample is devided into two; i.e. the society functioning as service client is big as 250 people, and the officials representing as government agent giving service as big as 50 people. The researcher wants to know if there is a difference on service perception between the society and officials, and then finds out whether the difference is influenced by their educational background, and finally figures out the perception of the society toward the service quality in the both regencies. The finding shows that there is a significant difference on the perception. It is summarized that the society expectation to get quality services from the officials cannot be fulfilled. It means that the service they get is lower than the expectation they have.